Progression of Aortic Calcification in Stage 4-5 Chronic Kidney Disease Patients Transitioning to Dialysis and Transplantation - Lankinen Roosa; Hakamäki Markus; Hellman Tapio; Koivuviita Niina S; Metsärinne Kaj; Järvisalo Mikko J (KARGER, 2022)
Background and Aims: Abdominal aortic calcification (AAC) is common in chronic kidney disease (CKD) patients and associated with increased mortality. Comparative data on the AAC score progression in CKD patients transitioning from conservative treatment to different modalities of renal replacement therapy (RRT) are lacking and were examined. Methods: 150 study patients underwent lateral lumbar radiograph to study AAC in the beginning of the study before commencing RRT (AAC1) and at 3 years of follow-up (AAC2). We examined the associations between repeated laboratory tests taken every 3 months, echocardiographic and clinical variables and AAC increment per year (ΔAAC), and the association between ΔAAC and outcomes during follow-up. Results: At the time of AAC2 measurement, 39 patients were on hemodialysis, 39 on peritoneal dialysis, 39 had a transplant, and 33 were on conservative treatment. Median AAC1 was 4.8 (0.5-9.0) and median AAC2 8.0 (1.5-12.0) (p < 0.0001). ΔAAC was similar across the treatment groups (p = 0.19). ΔAAC was independently associated with mean left ventricular mass index (LVMI) (log LVMI: β = 0.97, p = 0.02) and mean phosphorus through follow-up (log phosphorus: β = 1.19, p = 0.02) in the multivariable model. Time to transplantation was associated with Delta AAC in transplant recipients (per month on the waiting list: β = 0.04, p = 0.001). Delta AAC was associated with mortality (HR 1.427, 95% confidence interval 1.044-1.950, p = 0.03). Conclusion: AAC progresses rapidly in patients with CKD, and ΔAAC is similar across the CKD treatment groups including transplant recipients. The increment rate is associated with mortality and in transplant recipients with the time on the transplant waiting list.